Macroeconomics the Latin American way: Sunkel and the quest for a structuralist model - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2017)
The paper provides a narrative of the effort to develop a structuralist macroeconomic model in Latin America, as seen through the eyes of Chilean economist Osvaldo Sunkel (b. 1929). Sunkel faced the problem of how to model structuralism, an indigenous Latin American contribution to economics and to stabilization and development policies, put forward in the 1950s-1960s. It is shown how Sunkel deployed Schumpeter's 1954 distinction between "vision" and "scientific models", and how he took the Keynesian multiplier and Domar's growth equations as starting-points for his own formulations, instead of Lewis's 1954 model of a dual economy. Sunkel regretted the difficulties in formalizing the concept of "structure" and "structural" changes. Eventually, Sunkel became a co-founder of Latin American neo-structuralism in the 1990s, which is now regarded part of international heterodox economics in general.
Keywords: B22; B31; B50; 330; Sunkel; structuralism; models; Latin America; development macroeconomics